ANALISIS PANERAPAN MEKANISME AKAD MURABAHAH PADA PEMBIAYAAN MULTIGUNA KONSUMTIF DI PT BANK SUMUT SYARIAH KCP PANYABUNGAN - Nursantri Yanti; Silvia Fransiska (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The formulation of the problem in this study is "How is the application and mechanism of the murabaha contract on consumptive multi-purpose financing at PT Bank SUMUT Panyabungan Syariah Sub-Branch Office. This research focuses on the application and mechanism of the murabahah contract on consumptive multipurpose financing at PT Bank SUMUT Syariah Sub-Branch Office Panyabungan and to find out whether the application and mechanism of the murabahah contract on consumptive multipurpose financing are adjusted. This qualitative research uses primary and secondary data. Primary data was obtained from interviews with staff in the accounting department at the bank. The results show that the application of the murabahah contract in consumptive multipurpose financing at PT Bank SUMUT Syariah Sub-Branch Office Panyabungan has not been fully implemented in accordance with the requirements. There are two points that are not in line, namely "the customer's lack of knowledge about the contract to be made and the lack of incomplete files when making a contract". Because customers do not understand and understand Islamic finance, PT Bank SUMUT Syariah Sub-Branch Office Panyabungan has not fully implemented the provisions of the fatwa.